(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper investigates the relationship of attitude towards science and character ansions of understudy instructors. The example comprises of 30 understudy educators of Madurai dimer owenue region. A scale on Attitude towards Science was utilized to get the dato from the understudy. Rate analysis, ’t’ test second relationship were utilized for investigating the information. The outcome shows that there is a positive connection between’s Attitude towards Science and Personality Dimensions of Student Teachers.